The Complete Chloroplast Genome Sequences of 14 Curcuma Species: Insights Into Genome Evolution and Phylogenetic Relationships Within Zingiberales - Liang, Heng; Zhang, Yan; Deng, Jiabin; Gao, Gang; Ding, Chunbang; Zhang, Li; Yang, Ruiwu (Frontiers in Genetics, 2020)
Zingiberaceae is taxonomically complex family where species are perennial herb. However, lack of chloroplast genomic information severely hinders our understanding of Zingiberaceae species in the research of evolution and phylogenetic relationships. In this study, the complete chloroplast (cp) genomes of fourteen Curcuma species were assembled and characterized using next-generation sequencing. We compared the genome features, repeat sequences, sequence divergence, and constructed the phylogenetic relationships of the 25 Zingiberaceae species. In each Zingiberaceae species, the 25 complete chloroplast genomes ranging from 155,890 bp (Zingiber spectabile) to 164,101 bp (Lanxangia tsaoko)contained 111 genes consisting of 77 protein coding genes, 4 ribosomal RNAs and 30 transfer RNAs. These chloroplast genomes are similar to most angiosperm that consisted of a four-part circular DNA molecules. Moreover, the characteristics of the long repeats sequences and simple sequence repeats (SSRs) were found. Six divergent hotspots regions (matK-trnk, Rps16-trnQ, petN-psbM , rpl32, ndhA and ycf1) were identified in the 25 Zingiberaceae chloroplast genomes, which could be potential molecular markers. In addition to Wurfbainia longiligularis, the ψycf1 was discovered among the 25 Zingiberaceae species. The shared protein coding genes from 52 Zingiberales plants and four other family species as out groups were used to construct phylogenetic trees distinguished by maximum parsimony (MP), maximum likelihood (ML) and Bayesian inference (BI) and showed that Musaceae was the basal group in Zingiberales, and Curcuma had a close relationship with Stahlianthu. Besiedes this, Curcuma flaviflora was clustered together with Zingiber. Its distribution area (Southeast Asia) overlaps with the latter. Maybe hybridization occur in related groups within the same region. This may explain why Zingiberaceae species have a complex phylogeny, and more samples and genetic data were necessary to confirm their relationship. This study provide the reliable information and high-quality chloroplast genomes and genome resources for future Zingiberaceae research.